Performance evaluation of AODV in MASNETs: Study on different simulators - Mohamad Nazim, Jambli; W. B Wan, Mohd Shuhaimi; Halikul, Bin Lenando; Johari Yap, Abdullah; Sinarwati, Mohamad Suhaili (Institute of Electrical and Electronics Engineers Inc, 2015)
Nowadays, most of researchers working on Wireless Sensor Networks (WSNs) focus on Mobile Ad-hoc and Sensor Networks (MASNETs) due to their wide range of potential applications ranging from underwater monitoring to search and rescue mobile robotics applications. Most of these applications are deployed in remote and unattended areas. Since MASNETs are energy-constrained networks which have a low radio frequency coverage, their network topologies are frequently change due to mobile sensor nodes. In this paper, through extensive simulation of two different simulators namely Avrora and Castalia, we evaluated the capability of Ad-hoc On Demand Distance Vector (AODV) routing protocol on how far it can react to different speed and density of mobile nodes in MASNETs. We investigated the performance of AODV in terms of the average percentage of packet loss with the various speed and density of mobile nodes. Our performance study demonstrates that both simulators show the performance of AODV is significantly decreased in mobile environment due to the frequent topology change in MASNETs